EVALUATING THE EFFECTIVENESS OF A PBL-BASED ESP MODULE FOR NAVAL ARCHITECTURE STUDENTS - Antika, Rindilla; Asfina, Risda (LP2M Universitas Muslim Nusantara Al Washliyah, 2024)
This study explores the effectiveness of the English for Naval Architecture module based on Problem-Based Learning (PBL) in improving students' English proficiency in the context of naval architecture. The need for a specialized English module in this field arises from the specific language requirements faced by students in technical disciplines such as naval architecture. The research aims to assess how PBL-based instruction impacts students’ language skills, particularly in their ability to understand and apply technical English in real-world naval engineering scenarios. A pre-experimental with one group pretest - posttest research design was utilized. The data were collected through test to seek for the module’s effectiveness meanwhile questionnaires were employed to gather students’ feedback. The study involved 17 naval architecture students who used the PBL-based module over a semester. The effectiveness of the module was evaluated using N-Gain analysis, which revealed a moderate improvement in students' English proficiency with a score of 0.46. Additionally, student feedback indicated positive responses regarding the module’s structure, relevance, and its influence on skill development, especially in problem-solving, technical English usage, and critical thinking. While the improvement in English proficiency was moderate, the PBL approach significantly enhanced students’ ability to apply language skills in professional and technical contexts. Students also appreciated the module’s alignment with their field of study, and its real-world problem-solving activities engaged their interest. In conclusion, the English for Naval Architecture PBL module is an effective tool for teaching English in technical fields, offering a valuable model for future curriculum development in similar disciplines.